أحكام الأموال المكتسبة بين الزوجين في قانون الأسرة بدولة بروناي : دراسة فقهية تقويمية - Nur Ayuni binti Suhili (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research aims to study the property acquired during marriage (matrimonial property) under the Islamic Family Law of Brunei Darussalam. This research examines its position from the point of Islamic jurisprudence and discusses the views of some contemporary scholars pertaining to the division of property between spouses. This research also focuses on the claim of property under the Islamic Family Law of Brunei Darussalam as well as the articles related to property, its procedure and the division of property. Besides that, it explains the definition of property acquired during marriage under Islamic jurisprudence and Family Law of Brunei Darussalam. In order to verify if its application contradicts with Shariah or not, this research also presents some examples of cases which relate to the claim of property to see the extent of Shariah-compliance in its applications. This research adopted two research methods; inductive method which compiled information related to this research from primary and secondary resources as well as analytical method which was used to analyze the views of some contemporary scholars on the division of matrimonial property and the claim's procedure, divisions' criteria and cases related to this property to find out if its application contradicts with Shariah. This research also conducted personal interviews with officers at the Shariah Courts of Brunei Darussalam to gain related information about property acquired during marriage and its application in the Shariah courts of Brunei Darussalam. One of the main findings is that matrimonial property can be considered as a custom (norm) and does not contradict with Shariah. However, the number of cases related to this claim in Brunei is very few. Thus, the writer suggests the need to disseminate information about property acquired during marriage and maximize the awareness of Brunei society, especially spouses on their rights' on these property.